Pengaruh Pengetahuan, Promosi Dan Kualitas Pelayanan Terhadap Minat Nasabah Menggunakan Jasa Pegadaian Syariah (Studi Kasus Pada Pegadaian Syariah Kabupaten Kendal) - Muhamad Muljafar; Muhammad Agus Fauzi; Risti Lia Sari (Jurnal Rekoginisi Ekonomi Islam, 2023)
This study aims to analyze the effect of knowledge, promotion of service quality on customer interest in using sharia pawnshops. The object of this research is sharia pawnshop customers. This study uses convenience sampling method and the determination of the sample using the slovin formula obtained as many as 100 respondents. Data was collected using a questionnaire method distributed to 100 respondents, data processing using SPSS 22. Based on the results of the analysis using the t test with a significant level (5%) 0.05; it can be concluded that knowledge with a significant 0.66 < 0.05, no significant positive effect on customer interest, promotion 0.000 <0.05 has a significant positive effect on customer interest, service quality 0.074 < 0.05 has no significant positive effect on customer interest